The humongous book of SAT math problems : 650 math problems with comprehensive solutions, including the math sections from three full practice SATs : translated for people who don't speak math!! /: 650 math problems with comprehensive solutions, including the math sections from three full practice SATs : translated for people who don't speak math!!. ([2013]) - Kelley, W. Michael
No abstract available